Percutaneous radiofrequency ablation of pancreatic insulinoma: A case report and literature review - Hamidreza Rouientan, MD; Shahram Akhlaghpoor, MD (Radiology Case Reports)
Insulinomas are functional neuroendocrine neoplasms arising from the pancreatic islet cells resulting in excess insulin secretion and hypoglycemic episodes. Surgical resection is the standard treatment, but minimally invasive options such as radiofrequency ablation (RFA) have emerged as valuable alternatives, especially for nonsurgical candidates. We present the case of a 38-year-old male experiencing repeated episodes of critical hypoglycemia secondary to a pancreatic insulinoma, confirmed by elevated insulin and C-peptide levels and imaging findings. Initial surgical resection was unsuccessful due to intraoperative difficulty in localizing the lesion. The patient was subsequently treated with percutaneous RFA. Following the procedure, he developed mild pancreatitis, which was managed conservatively with complete resolution Follow-up at 12 months showed significant clinical improvement, normalization of insulin levels, and no evidence of tumor recurrence.